EFFECTS OF COOKING ON SOME PHYSICAL CHARACTERISTICS OF NERE SEEDS OR AFRICAN LOCUST BEANS (Parkia biglobosa) - AHOUANSOU, ROGER H.; SANYA, EMILE ADJIBADÉ; BAGAN, GONTRAND COMLAN; VIANOU, COKOU ANTOINE; HOUNHOUIGAN, DJIDJOHO JOSEPH (My University, 2010)
The major difficulty encountered in processing locust beans or nere seeds (Parkia biglobosa) into afitin subsist is the laborious seeds dehusking. Studies were conducted to determine the optimal cooking duration for ensuri-ng the seeds attained 16.14 % (db) water content prior to efficient dehusking. Therefore, the effects of cooking the seeds in water at 102 °C for duration of 1, 2, 3, 4, 5, and 6 hours on the physical characteristics were assess-ed. Depending on the treatment duration, the cooking induced variable modifications in the physical characteri-stics of the seeds. The water content, 1000-seeds mass, and 1000-seeds volume of cooked seeds increased with cooking duration, respectively from 16.14 to 284.62 % (db), 231.66 to 508.33 g and 208 to 482 cm3. Seed poro-sity rose from 35.6 to 42.2 % during the first hour of cooking, but decreased gradually to attain constant value of 41 % for the remaining 5 h. Although the average size of seeds increased marginally, there was corresponding lengthening, indicated by 20.40 % change in thickness, 14.5 % change in length and 13.5 % change in width, which confirmed the remarkable effects of cooking treatment. However, the true and bulk densities decreased respectively from 1110 to 1055 kg/m3 and 715 to 625 kg/m3 as cooking time increased. The data on dimension-al changes (seed length and width) and swelling as function of the cooking time provided parameters for design-ing shelling grids for efficient dehusking.
Keywords: African locust beans; cooking; dehusking; shelling; bulk density; dimensional and volumetric changes